Mosaicing Tool for Aerial Imagery from a Lidar Bathymetry Survey - Pe'eri, Shachak; Rzhanov, Yuri (The International Hydrographic Review, 2008)
Aerial imagery collected during lidar bathymetry surveying provides an independent reference dataset for ground truth. Mosaicing of aerial imagery requires some manual involvement by the operator, which is time consuming. This paper presents an automatic mosaicing procedure that creates a continuous and visually consistent photographic map of the imaged area. This study aimed to use only the frames from the aerial camera without additional information. A comparison between the features in the resultant mosaic and a reference chart shows that the mosaic is visually consistent and there is good spatial-geometric correlation of features.